Rapid paracellular transmigration of Campylobacter jejuni across polarized epithelial cells without affecting TER: Role of proteolytic-active HtrA cleaving E-cadherin but not fibronectin - Boehm, Manja; Hoy, Benjamin; Rohde, Manfred; Tegtmeyer, Nicole; Baek, Kristoffer T.; Oyarzabal, Omar A.; Brondsted, Lone; Wessler, Silja; Backert, Steffen (Gut Pathogens, 2012)
Background: Campylobacter jejuni is one of the most important bacterial pathogens causing food-borne illness worldwide. Crossing the intestinal epithelial barrier and host cell entry by C. jejuni is considered the primary reason of damage to the intestinal tissue, but the molecular mechanisms as well as major bacterial and host cell factors involved in this process are still widely unclear. Results: In the present study, we characterized the serine protease HtrA (high-temperature requirement A) of C. jejuni as a secreted virulence factor with important proteolytic functions. Infection studies and in vitro cleavage assays showed that C. jejunis HtrA triggers shedding of the extracellular E-cadherin NTF domain (90 kDa) of non-polarised INT-407 and polarized MKN-28 epithelial cells, but fibronectin was not cleaved as seen for H. pyloris HtrA. Deletion of the htrA gene in C. jejuni or expression of a protease-deficient S197A point mutant did not lead to loss of flagella or reduced bacterial motility, but led to severe defects in E-cadherin cleavage and transmigration of the bacteria across polarized MKN-28 cell layers. Unlike other highly invasive pathogens, transmigration across polarized cells by wild-type C. jejuni is highly efficient and is achieved within a few minutes of infection. Interestingly, E-cadherin cleavage by C. jejuni occurs in a limited fashion and transmigration required the intact flagella as well as HtrA protease activity, but does not reduce transepithelial electrical resistance (TER) as seen with Salmonella, Shigella, Listeria or Neisseria. Conclusion: These results suggest that HtrA-mediated E-cadherin cleavage is involved in rapid crossing of the epithelial barrier by C. jejuni via a very specific mechanismusing the paracellular route to reach basolateral surfaces, but does not cleave the fibronectin receptor which is necessary for cell entry. © 2012 Boehm et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Cellular invasion; E-cadherin; Fibronectin; HtrA; MKN-28; Molecular pathogenesis; Signaling; TER; Virulence